Chromosomal characteristics and karyotype evolution of oxyopidae spiders (araneae, entelegynae) - Stávale, L. M. [UNESP]; Schneider, M. C.; Brescovit, A. D.; Cella, D. M. [UNESP] (Genetics and Molecular Research, 2011)
We made a cytogenetic analysis of four species of Oxyopidae and compared it with the karyotype data of all species of this family. In Hamataliwa sp, the mitotic cells showed 2n♂ = 26+X 1X 2 and telocentric chromosomes. The 2n♂ = 28, which has been described for only one oxyopid spider, is the highest diploid number reported for this family. Peucetia species exhibited distinct karyotype characteristics, i.e., 2n♂ = 20+X 1X 2 in P. flava and 2n♂ = 20+X in P. rubrolineata, revealing interspecific chromosome variability within this genus. However, both Peucetia species exhibited telocentric chromosomes. The most unexpected karyotype was encountered in Oxyopes salticus, which presented 2n♂ = 10+X in most individuals and a predominance of biarmed chromosomes. Additionally, one male of the sample of O. salticus was heterozygous for a centric fusion that originated the first chromosomal pair and exhibited one supernumerary chromosome in some cells. Testicular nuclei of Hamataliwa sp and O. salticus revealed NORs on autosomal pairs, after silver impregnation. The majority of Oxyopidae spiders have their karyotype differentiated by both reduction in diploid number chromosome number and change of the sex chromosome system to X type; however, certain species retain the ancestral chromosome constitution 2n = 26+X1X2. The most remarkable karyotype differentiation occurred in O. salticus studied here, which showed the lowest diploid number ever observed in Oxyopidae and the second lowest registered for Entelegynae spiders. © FUNPEC-RP www.funpecrp.com.br.
Keywords: Chromosome fusion; Cytogenetic; Diploid number; Nucleolar organizer region; Sex chromosome system; animal cell; chromosome analysis; chromosome pairing; chromosome variant; diploidy; female; karyotype evolution; male; nonhuman; sex chromosome; species differentiation; spider; Animals; Cell Cycle; Chromosome Banding; Chromosomes, Insect; Diploidy; Evolution, Molecular; Female; Genetic Variation; Karyotyping; Male; Nucleolus Organizer Region; Sex Chromosomes; Spiders; Araneae; Entelegynae; Hamataliwa; Oxyopes salticus; Oxyopidae; Peucetia